Financial stability challenges in EU candidate and potential candidate countries - Francisco Ramon-Ballester; Daniela Pulst; Michaela Posch; Li Savelin; Stoyan Manolov; Ivan Huljak; Winona Kuhles; Ramona Jimborean; Christos Papazoglou; Zsolt Oláh; Bálint Dancsik; Andrea Colabella; et al. (European Central Bank (ECB), 2015)
This paper reviews financial stability challenges in countries preparing for EU membership, i.e. Albania, Bosnia and Herzegovina, Kosovo*, Iceland, the former Yugoslav Republic of Macedonia, Montenegro, Serbia and Turkey. The paper has been prepared by an expert group of staff from the European System of Central Banks (ESCB) in which experts from EU candidate and potential candidate country central banks also participated. The paper finds that near-term challenges to financial stability primarily relate to credit risks from the generally weak economic dynamics in combination with already high non-performing loan burdens in many banking systems, especially in the Western Balkans. In the medium-term, challenges to financial stability stem from indirect market risks to banks related to foreign currency lending as well as lingering exposures to funding risks, with Western Balkan economies again appearing as relatively more vulnerable. Looking further ahead, the paper highlights that the magnitude of the challenge to reach a `new banking normal' for banking systems in these countries appears to remain sizeable, while noting that the establishment of adequate home-host cooperation channels would be important to help maximise the potential benefits to third parties stemming from centralised banking supervision under the Single Supervisory Mechanism (SSM).
Keywords: F31; F34; F36; F41; G21; G28; 330; banking sector; banking union; cross-border flows; deleveraging; emerging markets; Europe; foreign exchange lending